Lake Peters water temperature and luminous flux, Alaska, 2015-2017 - Darrell Kaufman; David Fortin; Erik Schiefer; Lorna Thurston; Jason Geck; Michael Loso; Nicholas McKay; Anna Liljedahl (Arctic Data Center, 2019)
These datasets are measurements of lake temperature (°C) and luminous flux (Lux) collected at various water depths on moorings at Lake Peters. The moorings were equipped with Hobo pendants [UA-002] and Hobo Water Temp Pro loggers [H20-001] at different water depths to track the thermal structure of the lake. Moorings located in the central basin of the lake (two moorings at Station 7 and one mooring at Station 8) provide measurements from May 2015 until August 2016 (Station 7) and August 2015 until August 2017 (Station 8). A mooring in the distal basin (one mooring at Station 11) provides data from May 2015 to August 2015. A mooring in the proximal basin (one mooring at Station 3) provides data from May 2015 until August 2015.